2014
DOI: 10.1016/j.yjmcc.2014.02.007
|View full text |Cite
|
Sign up to set email alerts
|

PKA turnover by the REGγ-proteasome modulates FoxO1 cellular activity and VEGF-induced angiogenesis

Abstract: The REGγ-proteasome serves as a short-cut for the destruction of certain intact mammalian proteins in the absence of ubiquitin-and ATP. The biological roles of the proteasome activator REGγ are not completely understood. Here we demonstrate that REGγ controls degradation of protein kinase A catalytic subunit-α (PKAca) both in primary human umbilical vein endothelial cells (HUVECs) and mouse embryonic fibroblast cells (MEFs). Accumulation of PKAca in REGγ-deficient HUVECs or MEFs results in phosphorylation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 58 publications
2
23
0
Order By: Relevance
“…The REGγ gene is located in 17q21 in humans, a region with high genetic linkage to schizophrenia in Latino populations (Escamilla et al, 2009;Lewis et al, 2003) and implicated in several other CNS diseases, such as autism (Cantor et al, 2005), and bipolar disorder (Ewald et al, 2005), which share at least some symptoms with schizophrenia and schizoaffective disorders. Since the discovery of a mammalian target of REGγ, SRC3 (Steroid receptor co-activator protein; Li et al, 2006), accumulating evidence has revealed diverse functions for the ATP-and ubiquitin-independent REGγ-proteasome pathway, including regulation of cell cycle (Kobayashi et al, 2013;Li et al, 2007), angiogenesis (Liu et al, 2014), and hepatic lipid metabolism (Dong et al, 2013). REGγ is widely expressed in tissues , especially in the brain.…”
Section: Introductionmentioning
confidence: 99%
“…The REGγ gene is located in 17q21 in humans, a region with high genetic linkage to schizophrenia in Latino populations (Escamilla et al, 2009;Lewis et al, 2003) and implicated in several other CNS diseases, such as autism (Cantor et al, 2005), and bipolar disorder (Ewald et al, 2005), which share at least some symptoms with schizophrenia and schizoaffective disorders. Since the discovery of a mammalian target of REGγ, SRC3 (Steroid receptor co-activator protein; Li et al, 2006), accumulating evidence has revealed diverse functions for the ATP-and ubiquitin-independent REGγ-proteasome pathway, including regulation of cell cycle (Kobayashi et al, 2013;Li et al, 2007), angiogenesis (Liu et al, 2014), and hepatic lipid metabolism (Dong et al, 2013). REGγ is widely expressed in tissues , especially in the brain.…”
Section: Introductionmentioning
confidence: 99%
“…11 REGγ also affects angiogenesis by regulating PKA activity. 12 REGγ is conserved in Drosophila and one Drosophila Reg (identified as dReg) has been identified. 13 However, the biological function of dReg is largely unknown.…”
mentioning
confidence: 99%
“…Previous studies demonstrated that REGγ is overexpressed in multiple types of cancer including breast, thyroid, colorectal and liver cancers . A recent study found that REGγ promoted VEGF‐induced angiogenesis by regulating PKA signal pathway . Moreover, our previous study showed that REGγ promoted skin tumor development in a two‐stage skin carcinogenesis mouse model .…”
Section: Introductionmentioning
confidence: 89%